ISRAT DALAM KITAB HALAIN KARYA AHMAD AL-SA - Mahfud, Hakim (IAIN Kediri, 2019)
ISRAILIYYA<Tin HA<SHIYAH AL-SA<WIY ‘ALA TAFSI<>R JALA<LAINAttitudeSyaikhal-Sa>wiy Against ActsIsra>iIliyya>t(Attitude in the Book ofHa<shiyah) is based on the many history of Isra> iIliyya> t contained in Ha<shiyah al-S a>wiy so that the number of readers who are not selective about stories that are not necessarily true. The author examines the attitude of Syaikh al-Sa>wiy on the story of Israliyya>t contained in ha<shiyah al-sa<wiy ‘ala tafsi>r jala>layn. With the aim of knowing whether or not the critical attitude of Syaikh al-Sa>wiy towards the story of Isra>iIliyya>t. The author uses the Research library method (literature). To obtain information from various sources the author uses the Documentation method then analyzes the data using a discourse analysis method developed by Tuen A.van Djijk namely macro structure, superstructure, and microstructure. The results of this study revealed that: The attitude of Syaikh al-Sa>wiyon the story of Israliyya>t in Ha<shiyahnot all the stories of Israliyya>the commented. There are several stories that he included his sanad, but he immediately relies on the origin of history. There are also those who do not include the sanad at all. There are some narrations that he did not comment on and there is also a history that he commented on.Keyword: Israliyya>t, attitude of Shaihkal-Sa<wiy, and Ha<shiyah al-Sa<wiy